Increased macrolide resistance rate of Mycoplasma pneumoniae correlated with epidemic in Beijing, China in 2023 - Chen, Yujie; Jia, Xinyu; Gao, Yagang; Ren, Xue; Du, Bing; Zhao, Hanqing; Feng, Yanling; Xue, Guanhua; Cui, Jinghua; Gan, Lin; Feng, Junxia; Fan, Zheng; et al. (Frontiers in Microbiology, 2024)
We collected respiratory specimens from 128 pediatric patients diagnosed with pneumonia in Beijing in late 2023. Mycoplasma pneumoniae was detected in 77.3% (99/128) patients, with 36.4% (4/11), 82.9% (34/41), 80.3% (61/76) in children aged less than 3 years, 3-6 years, over 7 years, respectively. Mycoplasma pneumoniae was characterized using P1 gene typing, MLVA typing and sequencing of domain V of the 23S rRNA gene. P1 gene type 1 (P1-1) (76.1%, 54/71) and MLVA type 4-5-7-2 (73.7%, 73/99) were predominant. MLVA identified a new genotype: 3-4-6-2. Macrolide resistance-associated mutations were detected in 100% of samples, with A2063G accounting for¬¬ 99% and A2064G for 1%. The positive rate of M. pneumoniae was higher compared to previous reports, especially in children less than 3 years, suggesting a M. pneumoniae epidemic showing a younger age trend occurred in late 2023 in Beijing, China. Higher proportions of macrolide-resistant M. pneumoniae, P1-1 and 4-5-7-2 genotype M. pneumoniae indicated increased macrolide resistance rate and genotyping shift phenomenon, which might be attributable to this epidemic. Additionally, complete clinical information from 73 M. pneumoniae pneumonia inpatients were analyzed. The incidence of severe M. pneumoniae pneumonia was 56.2% (41/73). Mycoplasma pneumoniae pneumonia patients exhibited longer duration of fever, with a median value of 10.0 days (IQR, 8.0–13.0), and higher incidence of complications (74.0%, 54/73). However, in this cohort, we found that the severity of M. pneumoniae pneumonia, co-infection, or complications were not associated with M. pneumoniae P1 gene or MLVA types. Clinicians should be aware that patients infected with macrolide-resistant M. pneumoniae exhibited more severe clinical presentations.